An agenda for Australian rural sociology: Troubling the white middle-class farming woman. (June 2022) - Pini, Barbara; Rodriguez Castro, Laura; Mayes, Robyn
In reflecting on the last two decades of publications by Australian rural studies scholars in three major disciplinary journals, this article argues that the field of Australian rural sociology has failed to address racial inequality and class difference. While we note a burgeoning of feminist rural research challenging the historical emphasis on the white male farmer, this too has tended to occlude class and race, as is demonstrated in our analysis of the national 'Invisible Farmer' project. Accordingly, we point to a need to bring anti-racist work and scholarship to bear on our subdiscipline. In particular, we call for Australian rural studies scholars to engage with Aboriginal and/or Torres Strait Islander scholarship to interrogate whiteness as a category of difference and to open a discussion about relinquishing settler power, including in the academy. We emphasise the need for actions to understand and challenge the continuing dominance and privilege of whiteness and the fundamentally classed colonial project in Australian rural studies.